2009
DOI: 10.1016/j.jim.2009.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular fractionation of human eosinophils: Isolation of functional specific granules on isoosmotic density gradients

Abstract: Subcellular fractionation has been an important tool in investigating human eosinophil structure and function, including localizing of cytokine/chemokines within granules, investigating granule protein translocation and intracellular transport during eosinophil secretion, and studying secretory mechanisms of granules. The resolution of organelles obtained by subcellular fractionation was improved considerably after the introduction of nonionic iodinated density-gradient metrizamide and Nycodenz media that, unl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 27 publications
1
32
1
1
Order By: Relevance
“…Moreover, as shown in various allergic and other eosinophil-enriched diseases, some tissues may lack detectable intact eosinophils because these cells have already undergone cytolysis or degranulation; the prior presence of these cells is evidenced by extracellular eosinophil granules and/or granule-derived proteins, such as MBP1. Although electron microscopy is limited to an even greater extent by the small fields that are amenable to visualization, this technique has been used to detect extracellular, core-containing granules in tissues that could not be detected by conventional histological staining 8 , which has provided strong evidence of an association between eosinophil cell-free granules and disease pathology. Moreover, the generation of monoclonal antibodies raised against eosinophil granule proteins (such as MBP1 and EPX) has greatly enhanced the sensitivity of detecting tissue eosinophils by immunohistochemistry and immunofluorescence.…”
Section: Detecting Tissue-resident Eosinophilsmentioning
confidence: 99%
“…Moreover, as shown in various allergic and other eosinophil-enriched diseases, some tissues may lack detectable intact eosinophils because these cells have already undergone cytolysis or degranulation; the prior presence of these cells is evidenced by extracellular eosinophil granules and/or granule-derived proteins, such as MBP1. Although electron microscopy is limited to an even greater extent by the small fields that are amenable to visualization, this technique has been used to detect extracellular, core-containing granules in tissues that could not be detected by conventional histological staining 8 , which has provided strong evidence of an association between eosinophil cell-free granules and disease pathology. Moreover, the generation of monoclonal antibodies raised against eosinophil granule proteins (such as MBP1 and EPX) has greatly enhanced the sensitivity of detecting tissue eosinophils by immunohistochemistry and immunofluorescence.…”
Section: Detecting Tissue-resident Eosinophilsmentioning
confidence: 99%
“…Contaminating cells and DNA were removed by centrifugation at 200 3 g for 10 minutes, followed by incubation for 10 minutes with DNase I (20 U/mL; New England Biolabs, Ipswich, MA). Thereafter, supernatants were centrifuged at 2500 3 g for 10 minutes, and pelleted subcellular structures were stained as previously described in Neves et al 11 The gating strategy for flow cytometry was the same as for supplemental Figure 1. CellMask, LysoTracker, and CellTracker (Invitrogen) were used for microscopic analyses as described in supplemental "Materials" (supplemental Figure 7).…”
Section: Staining Of Granule-rich Subcellular Structuresmentioning
confidence: 99%
“…Cell-free eosinophil granules express ligand-binding cytokine, chemokine, and eicosanoid receptors on the surface of their delimiting membranes. 11,12 Cell-free human and mouse eosinophil granules with receptor-mediated activation of intragranule signaling pathways can directly secrete selected granule-derived proteins, including ECP, EPO, ribonucleases, and cytokines, for example, the interleukins IL-4 and IL-6. [12][13][14] Thus, the local tissue release of cell-free, secretion-competent eosinophil granules, secondary to eosinophil lysis, might constitute a means by which postmortem eosinophils could continue to provide immunoregulatory, pro-inflammatory, and other immunopathogenic stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Although intact, membrane-bound granules secreted by eosinophils have been widely observed at tissue sites associated with eosinophilic inflammation, their functional significance and ability to secrete preformed cationic proteins and cytokines have only recently become apparent [3,4,5,6,7]. Notably, it has been demonstrated that isolated human extracellular eosinophil granules are secretion-competent organelles.…”
Section: Eosinophil Cell-free Granules As ‘Cluster Bombs'mentioning
confidence: 99%